On the acquisition of prepositions - Alexaki, Christina; Kambanaros, Maria; Terzi, Arhonto (My University, 2007)
This work studies the acquisition of Greek Prepositional Phrases. We focus on locative prepositions, because they may combine a lexical and a functional element, hence, can offer insights for both the acquisition and the syntactic status of prepositions from this perspective. We found that both, se and apo, appear after the lexical part of complex prepositions, and fully develop after age three. We compare se and apo when part of complex prepositions and when conveying location/direction alone and conclude that the former may be acquired after the latter. Apo is also encountered much earlier alone, but only preceding locative adverbials
Keywords: Acquisition of Ps; Se; Apo; Complex Ps; Locatives